Parents Are Stressed! Patterns of Parent Stress Across COVID-19 - Adams, Elizabeth L.; Smith, Danyel; Caccavale, Laura J.; Bean, Melanie K. (Frontiers in Psychiatry, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic has caused numerous unexpected challenges for many families, and these long-lasting demands likely contribute to higher stress for parents. The aim of this study was to describe changes in parent stress longitudinally from before (retrospective) to two timepoints during COVID-19. Stressors that influenced parenting and strategies to manage parenting difficulties at each timepoint during COVID-19 are also described. Parents (N=433; 95% female) in the US with >1 child aged 5-18 years completed an online survey in May 2020 (T1; at the peak of stay-at-home mandates) and in September 2020 (T2; children’s return to school). Surveys included the 10-item Perceived Stress Scale (PSS) and questions on parenting-specific stress, stressors that influenced parenting, and strategies to manage parenting difficulties during COVID-19. Retrospective report of pre-COVID-19 stress was assessed at T1; current stress was assessed at T1 and T2. Repeated measures analysis of variance examined changes in stress over time. Parent’s stress increased from before COVID-19 to T1 (PSS score: 16.3±5.7 to 22.0±6.4, respectively; p<0.01), and decreased by T2 (19.2±6.0), but remained elevated above pre-COVID-19 values (p<0.01). Most parents (71.1%) reported an increase parenting-specific stress from before COVID-19 to T1, which continued to increase for 55% of parents at T2. Common stressors that impacted parenting during COVID-19 were changes in children’s routines, worry about COVID-19, and online schooling demands. Common strategies parents used to manage parenting difficulties included doing family activities together, keeping in touch with family/friends virtually, and keeping children on daily routines. Parent stress increased substantially during COVID-19 and has not returned to pre-COVID-19 levels, suggesting the need for enhanced mental health resources and supports. Public health interventions should address parenting-specific stressors and effective strategies for managing parenting difficulties to mitigate their deleterious impact.